OF HAMBRES AND FOMES: COMPARING ARGENTINE AND BRAZILIAN LAWS STRUCTURING THE MAIN PUBLIC POLICY ON THE RIGHT TO ADEQUATE FOOD - João Marcel Evaristo Guerra (REVISTA PARADIGMA, 2025)
This article aims to comparatively analyze Argentine Law No. 25,724, of December 27, 2002, which established the National Nutrition and Food Program, and Brazilian Law No. 11,346, of September 15, 2006, which created the National Food and Nutritional Security System – both foundational laws for public policies that implement the right to adequate food (RAF) and combat hunger. Four comparative criteria were established: i) history of the legislative procedure; ii) holders and beneficiaries of measures implementing the RAF provided by the legislation; iii) definition of institutes and concepts related to the RAF provided by law; and iv) models of distribution of responsibilities among federative entities. At the conclusion of the research, it was observed that Argentine law is more protective according to the first criterion, while Brazilian law is more protective according to the second criterion. According to the third and fourth criteria, it was found that a comparison between the two legal rules is not possible, since it is a fundamental decision of a political nature for each of the States.